Nonlinear Bending of Symmetrically Laminated and Homogeneous Anisotropic Plates - Prabhakara, M.K.; Chia, C.Y. (Engineering Transactions, 1977)
A large deflection analysis of symmetrically laminated anisotropic rectangular plates under transverse load is presented with homogeneous anisotropic plates treated as a special case. Solutions to the von Kármán-type large deflection equations expressed in terms of transverse deflection and force function are formulated in the form of double series for clamped and simply supported plates respectively. Numerical results are graphically presented for symmetric angle-ply and homogeneous graphite-epoxy square plates. In the case of small deflections the present results are in good agreement with the existing solutions.